Polen: Flüchtlingsnotstand – aber wo sind die Flüchtlinge? - Dietrich, Helmut (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2005)
Poland accepted the alien and asylum policy of the European Union. But what does it mean, in the face of the fact that most of the refugees don´t want to sojourn a lot of time in Poland, but want to join their families or friends in Western Europe? How the transfer of policies does work, if the local conditions are quite different than in Germany or France? The answer seems to be the dramatization of the refugee situation in Poland, especially the adoption of emergency measures towards refugees of Chechnya.